2021
DOI: 10.7554/elife.71263
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear transient amplification in recurrent neural networks with short-term plasticity

Abstract: To rapidly process information, neural circuits have to amplify specific activity patterns transiently. How the brain performs this nonlinear operation remains elusive. Hebbian assemblies are one possibility whereby strong recurrent excitatory connections boost neuronal activity. However, such Hebbian amplification is often associated with dynamical slowing of network dynamics, non-transient attractor states, and pathological run-away activity. Feedback inhibition can alleviate these effects but typically line… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 94 publications
0
17
0
Order By: Relevance
“…Further, recent evidence has shown that the short-term synaptic plasticity endows additional benefits beyond memory maintenance. For instance, it helps make recurrent networks more stable and more robust to perturbations and synaptic loss (Kozachkov et al, 2022; Wu and Zenke, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Further, recent evidence has shown that the short-term synaptic plasticity endows additional benefits beyond memory maintenance. For instance, it helps make recurrent networks more stable and more robust to perturbations and synaptic loss (Kozachkov et al, 2022; Wu and Zenke, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work identified the constraints on connectivity configurations in the SSN model that underlie such nonlinear activity responses as supersaturation [15], the paradoxical effect [47, 48], bistability, and persistent activity [28]. We show that the parameters of LIF spiking networks can be mapped to the SSN such that the same activity types emerge in the spiking network, according to the observations made with the SSN.…”
Section: Resultsmentioning
confidence: 81%
“…A recent review presented further experimental evidence and techniques used to study the inhibition-stabilized dynamics and discussed the ISN consequences for cortical computation [29]. In the SSN model [47, 48], a network is inhibition-stabilized if it fulfills the condition We note that in networks with a threshold linear transfer function, the analogous ISN condition only requires a strong recurrent coupling J EE > 1 and does not impose any constraints on the E firing rate level or the transfer function parameters [25, 29]. However, large enough J EE does not always guarantee that a recurrent neural network with a nonlinear transfer function is in the ISN regime.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations